P618 Long-term real-world data of Ustekinumab in Ulcerative Colitis – the Stockholm Ustekinumab study – STOCUSTE. (30th January 2023) - Sabhan, H
Abstract: Background: Background: Ustekinumab (UST) is an anti-interleukin-12/23 antibody in the treatment of inflammatory bowel disease (IBD), mainly used in patients failing anti-TNF-agents. The STOCUSTE study includes patients treated at four hospitals in Stockholm to provide long-term real-world data. Methods: Methods: This was a retrospective study including patients diagnosed with ulcerative colitis and treated with UST between years 2016 and 2021. The patients were followed from start of UST until withdrawal of treatment for any reason, or until end of study follow-up, July 31, 2021.We assessed disease activity; Physician Global Assessment (PGA); Ulcerative Colitis Endoscopic Index of Severity (UCEIS) score, laboratory parameters and drug persistence. The primary outcome was remission (PGA = 0) and response (decrease PGA ≥ 1 from baseline) at 3 and 12 months, respectively. Results: Results: 96 patients, 44 women and 52 men were included. The patients had either extensive colitis (68%), left-sided colitis (29%) or proctitis (3%). All but two patients were anti-TNF-experienced; 94 (98%) had failed ≥1, 59 (61%) ≥2 and 34 (35%) ≥3 anti-TNF-drugs. At inclusion 92 patients (96%) had active disease and 4 patients were in remission, 48 (50%) were on oral or topical corticosteroids, 13 (14%) had thiopurines. At 12 months only 9% were on oral or topical corticosteroids. Among patients who were treated with UST, 9/71 (6%) were in remission at 3 months, and 26/33 (78%) patients were in remission at 12 months. Withdrawal from treatment during the first 12 months was 36 (38 %), mainly due to persisting disease activity (20%); 8% were withdrawn due to adverse events, 2% needed bowel surgery, and 2% were lost to follow up. Conclusion: Conclusions: In this group of difficult-to-treat patients with ulcerative colitis, Ust was shown to be effective in the majority, with high drug persistence at 12 months in combination with a favorable safety profile.